2022
DOI: 10.2196/39181
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Telehealth Utilization and Policy Responses on COVID-19 in Japan: Interrupted Time-Series Analysis

Abstract: Background Telehealth using telephones or online communication is being promoted as a policy initiative in several countries. However, there is a lack of research on telehealth utilization in a country such as Japan that offers free access to medical care and regulates telehealth provision—particularly with respect to COVID-19. Objective The present study aimed to clarify telehealth utilization, the characteristics of patients and medical institutions u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As shown in emergency declaration in Japan, with most telemedicine provided via telephone and for prescription purposes. 27 In our study, we focused on monthly prescriptions, regardless of whether they were inperson or via telephone; therefore, the exact proportion is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in emergency declaration in Japan, with most telemedicine provided via telephone and for prescription purposes. 27 In our study, we focused on monthly prescriptions, regardless of whether they were inperson or via telephone; therefore, the exact proportion is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…found that the proportion of telemedicine use increased approximately threefold immediately following the first COVID‐19 emergency declaration in Japan, with most telemedicine provided via telephone and for prescription purposes. 27 In our study, we focused on monthly prescriptions, regardless of whether they were in‐person or via telephone; therefore, the exact proportion is unclear. However, it is possible that telephone prescriptions contributed to the continuation of treatment during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study conducted in Japan, where the mean age of respondents using telemedicine services was over 60 years. 12 This might be associated with the higher risk of developing chronic diseases, especially NCDs, in the aging population. 36 Most patients (65%) used telemedicine services for hypertension, DM, and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Patients over 65 years old used telemedicine services 3.25 times more than pre-pandemic, whereas patients under 65 years old used it 2.48 times more than pre-pandemic. 12 However, there is scarcity of information regarding the use of telemedicine service during the pandemic in Thailand. Moreover, there is limited information on the impact of COVID-19 variant outbreaks on the use of telemedicine services within Thailand and globally.…”
Section: Introductionmentioning
confidence: 99%
“…This research also highlights the importance of appropriate strategies for smart home design. The emergence of telehealth and online communication can play an essential role in successful aging in place, in that this telemedicine is an effective way to address many societal issues of older adults, such as overcrowding, driving a car, and mitigating infection risks [43]. A smart home with in-home monitoring technology can provide significant information to care providers, which will be helpful for maintaining health and well-being.…”
Section: Discussionmentioning
confidence: 99%